Efektivitas Pembelajaran TGT Berbasis CRT Pada Materi IPA Kelas VII SMP Muhammadiyah 1 Surakarta - Safitri, Eka Arnessya; Agustina, Lina (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This research aims to determine the effectiveness of TGT type cooperative learning based on CRT (Culturally Responsive Teaching) on science material at Surakarta Muhammadiyah Middle School. This research method is quasi-experimental research, with a sample of 42 students, data collection techniques using tests (post-test), interviews and observation. The data analysis technique for cognitive learning outcomes is in the form of a t test and affective learning outcomes in the form of descriptive statistics. The research results show that t test results with a significance value of 0.000 <0.05, then there is an effect of TGT type cooperative learning based on CRT (Culturally Responsive teaching) on the learning outcomes of seventh grade students of SMP Muhammadiyah 1 Surakarta.. Thus, it can be concluded that the application of the TGT type cooperative learning model based on CRT (Culturally Responsive Teaching) in science material in class VII SMP Muhammadiyah 1 Surakarta is included in the effective category.